Influence of Affect on Physical Activity: An Integrative Review. (September 2021) - Forster, Anna K.; Richards, Elizabeth A.; Foli, Karen J.; McGowan, Bethany; Hass, Zachary; Becker, Margaret; Miller, Ann
Affective states, such as feelings of anger and excitement, are linked to health outcomes and behaviors. The benefits of physical activity for individual affect is known; however, how affect influences physical activity participation is less understood. Using Whittemore and Knafl's framework, this integrative review examines the influence of affect on adult physical activity. using six databases, 19 articles published between 1997 and 2019. Themes found include support for the influence of positive affect on increased physical activity, a temporal aspect of affect, a variety of measurement tools, and varying uses of theoretical frameworks across studies. Advanced practice nurses and registered nurses may improve patient health behaviors, such as physical activity, by incorporating affect-focused assessments. Review findings support consideration of affect in physical activity counseling. Further research using theory-driven methods and consistent affect assessments is needed to test the complex relationship between affect and physical activity.